Create connections with your audience - Bachem, Jens (Henry Stewart Talks, 2010)
Connected kids and their parents, Today\s kids still want to talk and belong, They still spend time watching TV, Remember your childhood, Think local toy shop, Make sure they care, How commercial do you go?, Connect with the audience, Target ages and stages, Focus on integrated great ideas, Build and nurture connections